From mask to vaccine diplomacy: geopolitical competition in the Western Balkans - Tzifakis, N; Prelec, T (Ledizioni – LEDIpublishing, 2021)
One year after it landed in Europe, the Covid-19 pandemic has left a deep mark on the Western Balkans. On the one hand, it has exacerbated geopolitical dynamics that had been ongoing for decades, especially with regards to the activity of external actors. And while the EU has continued to be inconclusive, proceeding at a snail's pace with its carrot-and-stick approach, China has seized on the opportunity and expanded its footprint.